ANALISIS PENGGUNAAN MODEL-MODEL PEMBELAJARAN PADA MATA PELAJARAN SEJARAH KELAS XI SMAN 2 PONTIANAK - Nurul Retno Amalia; Aminuyati Aminuyati; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2021)
AbstractThis research aimed to determine the use of learning models in history subjects in class XI SMAN 2Pontianak. This research qualitative with a case study oncoming. Data collection techniques, used aninterviews, and documentation. The research subjects were history teachers and students. The resultsshowing: 1) how to determine the learning model of history subjects in class XI SMAN 2 Pontianak,namely adjusting the learning model with the material, time, available facilities and the abilities ofstudents 2)implementation of the learning model of history subjects class XI SMAN 2 Pontianak,namely by preparing lesson plans for learning models and preparing the material presented. 3)constraints in the use of learning models in history subjects in class XI SMAN 2 Pontianak, namely thelack of time in learning, facilities and infrastructure and class conditions that are less conducive. Effortsin overcoming the constraints of using learning models, namely estimating time allocation, motivatestudents and guide through explanations related to learning models.Keywords: Use, Learning Models, History Lessons